Contribution of Savings and Credit Cooperatives’ Services on the Socio-economic Development of their Members in Chitwan District, Nepal - Upreti, Dharma Raj (NPRC Journal of Multidisciplinary Research, 2026)
Background: Savings and Credit Cooperatives (SACCOs) are considered vital instruments for socioeconomic development, especially in developing nations like Nepal. However, empirical evidence on their specific contribution to members’ welfare remains limited. Objective: This study aimed to assess the contribution of SACCOs’ services—specifically saving, credit, and training—to the socioeconomic development of their members in Chitwan District, Nepal. Methods: Using a descriptive design, data were collected from 400 SACCO members via questionnaires. Quantitative analysis employed descriptive statistics (mean, standard deviation) and inferential techniques, including regression analysis and Pearson correlation. Findings: The results indicate a highly positive perception of SACCO services. Members reported high satisfaction with saving services, accessible credit with reasonable terms, and beneficial training programs. Regression analysis confirmed that credit, saving, and training services all significantly predict socioeconomic development. A strong positive correlation (r = 0.947) was found between overall SACCO services and members’ socioeconomic advancement. Conclusion: SACCO services in Chitwan District significantly enhance members’ financial inclusion, decision-making skills, and overall socioeconomic status. Implementation: To maximize impact, policymakers and SACCO managers should prioritize expanding financial education, maintaining supportive regulations, and raising public awareness of cooperative benefits.